“Nivel de corrosión en aleaciones usadas en prostodoncia dental en ambientes simulados de diferentes pH” - Piedra Paredes, Sebastián Gregorio (2019)
The purpose of this research is to analyze the corrosion level of two chromium nickel and cobalt chromium alloys that are subjected to three pH environments with artificial saliva (Salivsol) and to aging of the alloys in a thermocycler; the process started observing the structure through the optical microscope before being subject to aging in order to establish its state, then the aging procedure was performed in the thermocycler for 1000 cycles at three temperatures 55° , 5° and 37° ; for 4 days which is equivalent to an aging for one year, 3 chromium nickel alloys are placed, the same procedure is done with the cobalt chromium alloy, in the 10 days that are the alloys with the pH simulators is proceeded to observe the optical alloy microscope and set the pH, at 20 and 30 days the same procedure is performed in order to determine their effect on them and compare which of two alloys tend to corrosion levels. With the results obtained in the research is determined that the pH factors are divergent at the beginning and at the end. The research shows that in the two alloys the substance that most prones to corrosion was with the milk of magnesia and the corrosion levels however there is a coffee simulator that has greater resistance as a function of time.